The Role of Celebrity Endorsement on Impulse Buying Behavior with Customer Loyalty as a Moderating in the E-Commerce Industry - Sin Li; Umaidi Suhari; Muhammad Fajar Shidiqqi; Muhammad Aras; La Mani (Bina Nusantara University, 2023)
Purpose: Numerous studies have been conducted on celebrities to notice their effect on marketing. Celebrity endorsement has become one of the most popular marketing strategies, and Tokopedia as one of the most popular e-commerce websites in Indonesia also using these strategies for increasing their brand awareness. The purpose of this study is to explore other effects of celebrity endorsement on consumer behavior. This research aimed to define the impact of celebrities endorsement on consumer psychology, influencing impulsive buying behavior with consumer loyalty as a mediating variable. Research Methodology : This study applied quantitative survey with data was collected using an online questionnaire with sample characteristics were Tokopedia Customers and also a fan of the celebrity who lived in Indonesia by 442 samples using the purposive sampling method and data was conducted using the SmartPLS program. Result: This article indicated the findings that (1) celebrity endorsement had a positive impact on consumer loyalty, (2) a positive effect either directly or indirectly on impulsive buying behavior, and (3) consumer loyalty itself had a positive effect on impulsive buying behavior. Conclusions: This study proposes significant implications about how celebrity endorsement works and how it impacts customer behavior in the e-commerce Industry.